Legal Protection for Children as Victims of Incest Committed by Biological Fathers From a Victimology Perspective (Study at the Criminal Investigation Unit of the Banyumas Regency Woman and Children) - Wahyuningrum, Rengganis Rahma Esa; Hendriana, Rani; Angkasa (LPPM Universitas Harapan Bangsa, 2025)
Incest is a sexual relationship that occurs between family members, and in this case the child becomes a victim of incest. Therefore, legal protection is needed to fulfill the rights of children who are victims of incest. This research aims to determine the legal protection provided by the Criminal Investigation Unit of the Banyumas Regency Women and Children Protection Unit. This research is empirical juridical research with a qualitative approach method and the research specifications are analytical descriptive. The data used in this writing are primary data and secondary data. The data is then processed using reduction methods, data display and data categorization and then presented in the form of narrative text, charts and graphs. The results of this research show the provision of legal protection in the form of applying for restitution, providing shelter or safe houses, medical and psychological rehabilitation for children who are victims of incest. Furthermore, the inhibiting factors of the legal structure are the lack of human resources, such as the unavailability of psychiatrists and/or forensic psychologists to handle and resolve victims' trauma due to the events that occurred, as well as the lack of budget for post-mortems. Finally, regarding facilities and infrastructure, the Criminal Investigation Unit of the Banyumas Regency Women and Children Protection Unit does not provide shelter or safe houses for victims. Furthermore, from the legal substance, namely the absence of specific regulations governing incest, while from the legal culture factor there is a negative stigma from society which views victims as disdainful, and considers incest a disgrace so that victims feel afraid and embarrassed to report it to the authorities, including The existence of patriarchal culture and superior attitudes from men makes women powerless and unable to resist.